Implementation study of authentic assessment in physical education in Indonesia and Malaysia - Hariadi, Hariadi; Valianto, Budi; Akhmad, Imran; Syed Ali, Syed Kamaruzaman bin (Jurnal Cakrawala Pendidikan, 2025)
Authentic assessment is essential in physical education, sports, and health, encompassing cognitive, affective, and psychomotor dimensions. Despite the existence of assessment tools for fundamental movements, their widespread adoption remains limited. This study aims to assess the viability of the Instrument for Authentic Assessment in Physical Education (IPOPJ) within Indonesian and Malaysian elementary schools, offering a comparative analysis of the educational systems in both countries. The research objectives encompass understanding the implementation process of IPOPJ, identifying obstacles, and evaluating adherence to predefined standards. Employing concurrent triangulation, the study gathers quantitative data through questionnaires and qualitative data through observations and interviews. Analysis is focused on communication, resource availability, disposition, and bureaucratic structures. Findings from statistical analyses using Z-tests and concurrent triangulation reveal the absence of significant differences in responses from physical education teachers in Indonesia and Malaysia, indicating a high chance of IPOPJ implementation success in both countries. This study underscores the important role of effective communication, adequate resources, positive disposition, and streamlined bureaucratic structures in facilitating successful assessment implementation.